PERANAN PEMERINTAH DAERAH DALAM REKRUITMEN PEGAWAI (Studi Terhadap Peranan Badan Kepegawaian Daerah Di Kabupaten Sambas) - Sri Noviana E.42009005 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2021)
This essay aims to show and analyze the role of local civil service agency (bkd) in the recruitment of civil servants as well as the constraints that exist in the recruitment process. This essay title based on the problems raised in the recruitment of civil servants in Sambas reency that is still there is no official received their needs, so that these conditions give rise to lack of professionalism in the department ranked in Sambas regency office. This research uses descriptive type of research with a qualitative approach. research done through such as collecting research, acquire theories and regulations used as a foundation in research and field studies purporting to acquire data directly. Conclusion in this study is, recruitment planning by the organization. governance before the moratorium should according on position analysis. it has been in Government Regulation No. 11 of 2002 which means the procurement of civil servants carried out on the basis of needs, both in terms of quantity and quality of employees and job competency is required. position analysis is very important because by doing job analysis will be obtained by prospective civil servants in accordance with the field of science / knowledge that will be filled. other than that job analysis is needed in the placement of civil servants, because the job analysis will be obtained a clear picture of the needs of an office and workers' ability to meet those needs.Keywords: part, civil servants, recruitment, BKD